Precision Molecular Pathology of Lung Cancer (Molecular Pathology Library,, 2018)
This new edition provides the latest information and insights into the molecular basis for lung cancer. Since the publication of the previous edition of this volume, dramatic changes have occurred with the classification of lung cancer, biomarker testing, and molecular therapy. The book covers these changes, providing updates and new insights on the background of lung cancer, testing methods, and the molecular pathology of specific cell types, including adenocarcinoma, squamous cell carcinoma, small cell carcinoma, and precursor and preinvasive lesions. Authored by experts in the field, Precision Molecular Pathology of Lung Cancer, Second Edition remains one of the few books that comprehensively covers the new molecular pathology of lung cancer and is a valuable resource for pathologists, medical oncologists, radiation oncologists, thoracic surgeons, and thoracic radiologists.